2017
DOI: 10.1038/ncomms15805
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic loci associated with heart rate variability and their effects on cardiac disease risk

Abstract: Reduced cardiac vagal control reflected in low heart rate variability (HRV) is associated with greater risks for cardiac morbidity and mortality. In two-stage meta-analyses of genome-wide association studies for three HRV traits in up to 53,174 individuals of European ancestry, we detect 17 genome-wide significant SNPs in eight loci. HRV SNPs tag non-synonymous SNPs (in NDUFA11 and KIAA1755), expression quantitative trait loci (eQTLs) (influencing GNG11, RGS6 and NEO1), or are located in genes preferentially e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
112
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 109 publications
(116 citation statements)
references
References 71 publications
4
112
0
Order By: Relevance
“…GWAS data for HR and RMSSD were derived from Den Hoed et al (), n = 85,787 and Nolte et al (), n = 26,78, respectively. GWAS data for the major depressive disorder were derived from the GWAS summary statistics publicly released by the Psychiatric GWAS Consortium, excluding the dataset from 23andMe ( n = 173,005; Ripke et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…GWAS data for HR and RMSSD were derived from Den Hoed et al (), n = 85,787 and Nolte et al (), n = 26,78, respectively. GWAS data for the major depressive disorder were derived from the GWAS summary statistics publicly released by the Psychiatric GWAS Consortium, excluding the dataset from 23andMe ( n = 173,005; Ripke et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…of observations = 6,994), one of the largest and longest follow‐up (FU) studies allowing to examine the relationship of depressive and anxiety disorders and antidepressant use with cardiac autonomic activity. These data were combined with results from large genome‐wide association studies (GWAS) to compute polygenic risk scores (PRS) for depression (Ripke et al, ), resting HR (Den Hoed et al, ), and the root mean square of differences between successive interbeat intervals (RMSSD, a frequently used measure of HRV; Nolte et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, a genetic correlation between depression and HRV frequency domain metrics in adults (aged 47–60 years) has been found (Su et al 2010). Relatedly, the search for molecular genetic mechanisms underlying HRV is underway (Nolte et al 2017) and future research, with increasingly larger sample sizes, will be needed to explain the genetic variance estimated in heritability studies. It also appears that much of the variance of HRV is accounted for by individual environment, some of which changes between even ultra short (2.5-min) intervals, and therefore specific environmental factors (e.g., early life stressors) affecting autonomic health and overall cardiac health in adolescents should be explored.…”
Section: Discussionmentioning
confidence: 99%
“…To increase our understanding of potentially mediating mechanisms at the genetic variant level we searched the literature and the GWAS-catalog for previously reported variants. Of the 23 loci, eleven are in high LD (r 2 >0.6) with previously identified SNPs for resting heart rate 24,45 or heart rate variability 23 (Supplementary Table 9). A wider search in the GWAS-catalog revealed that SNPs in high LD (r 2 >0.6) with rs61765646 (NEGR1) were reported for the association with obesity; rs17362588 (CCDC141/TTN, but not the independent SNP rs35596070) and rs12906962 (MCTP2) with diastolic blood pressure, rs7072737 (PAX2) with systolic blood pressure; rs4963772 (BCAT1) with PR-interval and rs1997571 (CAV1) with atrial fibrillation and PR interval (Supplementary Table 10).…”
Section: Insights Into Pleiotropy and Clinical Relevancymentioning
confidence: 96%